Innovation capability among tourism SMEs in Kelantan/ Fadhilahanim Aryani Abdullah and Ruzanifah Kosnin - Abdullah, Fadhilahanim Aryani; Kosnin, Ruzanifah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Innovation capability is central to small and medium enterprises (SMEs) in order to compete with larger competitors. The main objective of this research is to investigate the role of research and development (R&D), technology, entrepreneurial leadership, and networking towards innovation capability among SMEs tourism players in Kelantan. Using a quantitative approach, an online self-administered questionnaire was gathered from tourism-related SMEs in Kelantan. 380 datasets were collected through email and analyzed using SPSS. Findings show that R&D, technology, entrepreneurial leadership, and networking have a significant contribution towards the innovation capability of tourism SMEs in Kelantan. Contribution to the body of knowledge and SMEs tourism players are highlighted.